Design of an ultrasound appointment system based on a patient-centered real-time dynamic resource allocation strategy - Zhang, Yong; Luo, Yan; Qiu, Li; Zhu, Ying; Lu, Xiao (Frontiers in Public Health, 2025)
IntroductionThe existing ultrasound appointment system faces multiple challenges, including a lack of diversity in its operation modes, sluggish efficiency, and limited flexibility. During emergency situations, such as disease outbreaks or severe disaster events, the demand for ultrasound examinations skyrockets, making it imperative to offer patients efficient and user-friendly ultrasound appointment services.MethodsThis study introduces the application of a patient-centered real-time dynamic resource allocation strategy in an ultrasound appointment system. This strategy focuses on the demand of patients, builds a multichannel and multimode ultrasound appointment system, and opens sets of parameters related to ultrasound appointments, such as examination room attributes, workload adjustments, and mutually exclusive rules of medical orders. The system can display patient appointment data in real time and carry out statistical analysis, and medical resources can be flexibly configured according to the patient appointment situation to fully meet the needs of patients. Moreover, the system interconnects the appointment data with the registration system and the examination room examination list to further optimize the medical service process.ResultsData such as the proportion of appointment channels, appointment time, and the quality and efficiency of ultrasound examinations before and after the introduction of the appointment system were compared and analyzed. According to the statistics, the proportion of online bookings increased from 0% to 81.42%. The average appointment times of general ultrasound examination and specialist ultrasound examination were reduced by 90.7% and 78.86%, respectively. The appointment staff was saved by 4 people, the average waiting time of patients in the examination area was reduced from 42 min to 11 min, and the number of ultrasound examinations was increased by 11.5%, while the number of error reports was also significantly reduced.DiscussionThe results show that the application of this strategy in an ultrasound appointment system is feasible and efficient. Patients can participate more in the entire process of ultrasound appointment and examination, obtain reliable ultrasound medical services faster and more efficiently, improve the diagnosis and treatment environment and order of the hospital, and optimize the medical service process.